Approach for selecting requirement elicitation technique - Hussein, Ibrahim Hassan (2019)
Requirements elicitation is an initial phase in software development. In this phase, requirements engineers gather the requirements of the software under development from users, stakeholders and customers. The techniques used for gathering requirements have a big influence on the quality of requirements and the success of project. Many requirements elicitation techniques (RET) such as: interview, prototype and observation can be used for requirements gathering process. One technique is not suitable for all different projects. Usually Requirement engineers select the RET based on personal preferences and assumptions such as; this is the only technique which they know. However, this subjective decision can result using inappropriate RET. Using unsuitable RET may decrease the quality of elicited requirements. Even though researchers proposed many techniques for elicitation, one of the challenging issues is to choose the suitable RET for specific situation. As result, the main purpose of this project is to help requirement engineers to choose suitable RET. To do that firstly, we identified factors that affect selecting RET. Secondly, approach to select suitable RET proposed. Thirdly, prototype developed to help requirements engineers to and ease the process of elicitation technique selection. Lastly experts invited to evaluate proposed approach and the prototype.